Penjualan Minyak Oplosan dalam Perspektif Hukum Ekonomi Syariah dan Perlindungan Konsumen: Studi Kasus Minyakita - Aura Nur Halizah; Baidhowi Baidhowi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Cooking oil is an essential necessity for society, prompting the government to introduce Minyakita with a set Maximum Retail Price (HET) to maintain price stability and availability. However, in practice, various fraudulent activities have been found in the distribution of cooking oil, one of which is the sale of adulterated oil mixed with low-quality oil or harmful substances. This practice not only financially harms consumers but also poses serious health risks. From the perspective of Sharia Economic Law, selling adulterated oil is categorized as tadlis (fraud), gharar (uncertainty), maysir (harmful speculation), and dharar (consumer harm), which contradict the principles of Islamic trade. Meanwhile, under consumer protection law, this practice violates Law No. 8 of 1999 on Consumer Protection and other regulations related to food safety standards. This study employs a normative legal research method with a qualitative approach through literature studies. The findings indicate that strict government oversight, consumer education, and stricter law enforcement are necessary to prevent the circulation of adulterated cooking oil. Synergy between regulators, business actors, and society is crucial to ensuring fair transactions in accordance with Sharia principles and consumer protection laws.